Holdaway Cephalometric analysis of soft tissue profile in peruvian adults - Orellana Manrique, Tomás Oriel (2007)
The purpose of this study was to determine characteristics of soft-tissue profile in peruvian adults using Holdaway linear and angular measurements. It was also the purpose of this study to compare the collected data with the Caucasian norms of Holdaway. The sample consisted of 40 untreated adults (20 males and 20 females) between 18 to 30 ages. The subjects selected were in good health and had normal occlusion. Lateral cephalogram x-rays were taken with the teeth in occlusion. The findings indicated that the most of linear and angular values were significantly different from those of the Holdaway analysis. The angle “H” in the Peruvian sample was 8.45° more than that of the American. Caucasian group.